Immune checkpoint inhibitors alone or in combination with chemotherapy for treatment of advanced non-small cell lung cancer after first-line platinum-based chemotherapy: A propensity score matching analysis - Qiu, Lupeng; Gao, Shan; Du, Sicheng; Sun, Shengjie; Liang, Yanjie; Sun, Zhuoya; Li, Tao; Jia, Guhe; Li, Ke; Sun, Xiaohui; Jiao, Shunchang; Zhao, Xiao (Frontiers in Oncology, 2022)
Objectives: Immune checkpoint inhibitors (ICIs) have changed the treatment landscape of several cancer types. However, data are lacking with regard to the clinical responsiveness of ICIs in patients with advanced non-small cell lung cancer (NSCLC) after standard first-line chemotherapy. Therefore, we aimed to evaluate the clinical efficacy of ICI alone or in combination with chemotherapy for patients with advanced NSCLC after first-line platinum-based chemotherapy. Materials and Methods: We retrospectively collected patients with confirmed advanced NSCLC who underwent ICI monotherapy or ICI plus chemotherapy after first-line platinum-based chemotherapy between January 2018 and December 2020. A propensity score matching analysis was used to balance baseline characteristics between the two treatment groups. Kaplan-Meier methods and multivariable Cox regressions were used for survival analyses. Results: Among 832 eligible patients, 222 received ICI monotherapy and 610 received ICI plus chemotherapy. The median overall survival (OS) of patients who received ICI plus chemotherapy was 16.0 months compared with 13.1 months in patients who received ICI monotherapy (HR: 0.64, 95% CI: 0.49-0.85, P = 0.002). After 1:1 propensity score matching, all baseline characteristics were well-balanced between the two treatment groups. Patients who received ICI plus chemotherapy had significantly longer OS than those who received ICI monotherapy (NR vs. 13.1 months, HR: 0.50, 95% CI: 0.34-0.71, P < 0.001). Meanwhile, the median time to treatment discontinuation was 4.4 months in the ICI-chemo group and 3.5 months in the ICI-mono group (HR: 0.72, 95% CI: 0.58-0.89, P = 0.002). The multivariate analysis indicated that treatment regimen was an independent prognostic factor for OS (HR: 0.488, 95% CI: 0.337-0.707, P < 0.001). Moreover, a nomogram that integrated both treatment regimens and clinicopathological factors was created for survival prediction. Conclusion: Our study indicated that patients with advanced NSCLC who received ICI plus chemotherapy after first-line platinum-based chemotherapy tended to have longer OS than those who received ICI monotherapy. The multivariate analysis showed that treatment regimen was an independent prognostic factor for OS. Future prospective studies are needed to confirm these findings.